Impaired suppressive capacity of activation-induced regulatory B cells in systemic lupus erythematosus - Gao, Nele Xian-Tai; Dresel, Julia; Eckstein, Volker; Gellert, Rimma; Ostermann, Hannah; Venigalla, Ram Kumar Chowdary; Schwenger, Vedat; Max, Regina; Blank, Norbert; Lorenz, Hanns-Martin; Tretter, Theresa (Arthritis & rheumatology, 2014)
Objective B cells with immunoregulatory properties (Breg cells) have been described in mice, but their role in the control of human immune responses is not well defined. We recently identified a human population of activated FSChigh B cells that exhibited regulatory activity toward T helper cells. The aim of the present study was to test such induced Breg (iBreg) cells in patients with autoimmune disease. Methods Purified CD19+FSChigh B cells derived from patients with systemic lupus erythematosus (SLE) or from healthy donors, which were activated via their B cell receptor, were cocultured with CD3-stimulated CD4+ T helper cells from SLE patients or healthy donors. 3H-thymidine incorporation, flow cytometry, and enzyme-linked immunosorbent assay (ELISA) were used to analyze proliferation, cytokine secretion, and surface marker expression. Results Although under costimulatory conditions, FSChigh SLE B cells supported the proliferation of healthy donor T cells to a similar extent as donor B cells, their regulatory function was significantly diminished in B cell suppressor assays. Similar effects were seen when SLE T cells were used, confirming that SLE T cells were equally susceptible to iBreg cell signals as healthy donor T cells and that SLE iBreg cell defects were independent of T cell origin. B cell viability and expression of surface markers (CD25, CD80, and B7-H1) or cytokines (interleukin-6 [IL-6], tumor necrosis factor α, and IL-10) were comparable in the two B cell populations. There was no correlation between the extent of iBreg cell-induced inhibition and disease activity. CD19+FSChigh B cells from patients with another systemic autoimmune disease, granulomatosis with polyangiitis (Wegener's) (GPA), exhibited no regulatory defects, which suggests that the iBreg cell defects were SLE-specific and not a general consequence of autoimmunity or inflammation. Conclusion Induced Breg cells from SLE patients, but not GPA patients, are less effective in the control of T helper cell proliferation, which supports the reported skewed B cell repertoire in SLE. The malfunctioning SLE iBreg cells might allow the overstimulation of immune responses and contribute to the initiation and/or perpetuation of disease.
Gesehen am 21.07.2020